(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: Noise Induced Hearing Loss (NIHL) is an occupational health hazard linked with noise exposure of more than 85 dB. Aircraft noise and other occupational noise exposure cause military aviators more susceptible to NIHL than commercial jet pilots. Aim: To find out the prevalence of noise induced hearing loss among different military aircrew population with special emphasis on identifying the associated risk factors. Materials and Methods: This cross sectional study was conducted on Kuwait Air force pilots those who came for annual medical checkup from July 2010 to July 2012. Audiometry of all subjects was done by ENT specialist and necessary data were collected by structured questionnaires. All data were analyzed by SPSS (Statistical Package for the Social Sciences) version 17.0 Results: Out of 221 aircrew 32 (14.48%) developed NIHL. Hearing loss was mild to moderate and predominately at high frequencies. Most affected group was helicopter pilots. Pilots of more than 40 years of age and those who had more than 1000 flying hours had mean hearing threshold more than other groups. The right ear was affected in majority of cases than left ear. Conclusion: Noise exposure to aircrew is inevitable so hearing loss prevention strategies might play a pivotal role to save aircrew hearing. Active surveillance of hearing protection practices might have beneficiary effect. Steps can be taken for early detection of NIHL and hearing conservation program. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18721 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 19-24